Capitalizing on Digital Health Care for Speech-Language Pathology and Audiology Professions to Be Contextually Relevant, Responsive, and Responsible in South Africa: A Narrative Review - Khoza-Shangase, Katijah (Journal of speech, language, and hearing research, 2025)
The integration of digital health care technologies into speech-language pathology and audiology is rapidly transforming service delivery. In South Africa and other low- and middle-income countries (LMICs), digital tools offer significant opportunities to address access challenges and enhance patient outcomes. However, the adoption of these technologies requires careful consideration of contextual factors. This study is a narrative review that analyzes the role of digital health care in speech-language pathology and audiology within the South African and LMIC context. A narrative review of 64 studies was conducted, extracting and synthesizing data into key thematic areas. The synthesis focused on the impact of digital health care on service delivery, training and capacity building, ethical challenges, and policy implications. The results highlight opportunities and challenges associated with digital health care implementation in speech-language pathology and audiology. Findings reveal five major themes in line with study objectives: (a) Digital health care enhances accessibility and equity in speech-language pathology and audiology services, particularly through telehealth and mobile applications; (b) artificial intelligence-driven diagnostics and personalized interventions improve efficiency and patient outcomes; (c) barriers include infrastructure deficits, regulatory gaps, and digital literacy challenges; (d) ethical and cultural considerations must be addressed to ensure inclusivity and equitable care; and (e) professional training and continuous professional development are critical for equipping practitioners with the necessary skills to integrate digital tools into clinical practice effectively. Digital health care presents a transformative opportunity for speech-language pathology and audiology, but its success in South Africa and LMICs depends on targeted investments, policy alignment, and culturally responsive implementation. Key recommendations include expanding digital infrastructure, integrating digital health care training into academic curricula, establishing regulatory and ethical guidelines, and promoting research on the contextual adaptation of digital tools. By embracing these strategies, speech-language pathology and audiology professions can enhance service delivery; improve patient outcomes; and ensure digital health care is contextually relevant, responsive, and responsible. https://doi.org/10.23641/asha.29997847.